Hearing Outcomes with Percutaneous and Transcutaneous BAHA® Technology in Conductive and Mixed Hearing Loss. Issue 9 (October 2021) - Tobia, Amjad; Yehudai, Noam; Khnifes, Riad; Shpak, Talma; Roth, Osnat; Khayr, Ranin; Luntz, Michal
Abstract : Objectives: To evaluate outcomes of BAHA Connect ® and BAHA Attract ® implantations, and to examine the prognostic utility of a preimplantation Softband ® -attached processor trial. Study Design: Retrospective case review Setting: Tertiary referral center. Patients: Patients who underwent Connect ® (19 ears) and Attract ® (25 ears) implantation between 2007 and 2017. Intervention: BAHA ® implantation. Main Outcome Measures: Unaided air conduction (AC), bone conduction (BC), and speech reception thresholds (SRTs), as well as free field (FF) aided with Softband ® -attached processor and with implant-attached processor thresholds. Results: Serviceable implant-attached processor PTA0.5, 1, 2 kHz (⩽35 dB HL) was achieved in 89 and 88% of the Connect ® and the Attract ® ears, respectively, while at 4 kHz this was achieved in 68 and 32% of the Connect ® and the Attract ® ears, respectively ( p   =   0.032 ). Significantly more Connect ® ears showed alignment between FF aided with implant-attached processors thresholds and BC thresholds. The alignment between the Softband ® -attached processors thresholds and implant-attached processors thresholds was similar in the two groups. Both groups exhibited similar positive improvement in the quality of life questionnaires Conclusions: Accessibility to sound with the implant-attached processor is well predicted by the pre-implantation Softband ® trial, both in the BAHA Connect ® and in the BAHA Attract ® ears. Hearing rehabilitation targets at 0.5, 1, and 2 kHz are met by most Connect ® and Attract ® ears, while at 4 kHz the outcome with Attract ® is poorer. This information should be presented to the patient during consultation prior to a decision as to the type of BAHA ® device to be implanted.